PENGARUH KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA CV. ER FROZEN MART DI DEPOK - Zendrato, Yuniria; Astuti, Indri; Saraswati, Yenita (Sekolah Tinggi Manajemen IMMI Jakarta, 2023)
Leadership is someone who has the ability to lead such as qualified intelligence, creative in giving directions to his subordinates, honest in all matters of work. Performance is the result of work that can be achieved by a person or group of people in a company in accordance with the authority and responsibility of each in an effort to achieve goals. The purpose of this study was to determine the influence of the variable Compensation on Employee Performance at CV. ER Frozen Mart in Depok. The sampling technique used in this study the authors used the Total Sampling Technique or as a whole. Where each population has the same opportunity to be selected as a sample, a total of 30 employees. Based on the results of the regression analysis that it turns out that the leadership variable can improve employee performance, the equation value Y = 9.833 + 0.803 X, there is a positive effect on employee performance, it is necessary to prove it by testing the hypothesis that the tcount value is = 9.272 the ttable value at (28) is = 1.701, then Ho is rejected and Ha is accepted means having evidence, that leadership has a very significant influence on employee performance. So the results of the analysis show that there is a positive influence of leadership on employee performance, a value of 0.842 is obtained so that it can be concluded that the influence is very strong or the coefficient of determination (KD) is 71.0%. So the level of influence is 71.0% and the remaining 29.0% is influenced by other factors which are not fully observed by the author.